Analisis Pengaruh Profitabilitas Dan Growth Opportunity Terhadap Nilai Perusahaan (Dengan Struktur Modal Sebagai Variabel Intervening) Pada Perusahaan Property Dan Real Estate Yang Terdaftar Di BEI Periode 2012-2014 - Pratama, Anggriawan Yoga; , Dra. Wafiatun Mukharomah, MM (2016)
Firm value is an investors perception about company's level of success. One of indicators that can be used by investors to find out the firm value is profitability. Profitability is closely connected with the firm value, because the company's ability to generate profits in its operations is the main aim of the company. In addition to profitability, there are also other factors that is growth opportunity and capital structure. This study aimed to test the influence of profitability, growth opportunity against the firm value with capital structure as intervening variable. This research aims to test the influence of profitability, growth opportunity against the value of the company's capital structure as an intervening variable. This research was conducted on the company's property and real estate registered in BEI period 2012-2014. With the method of purposive sampling, obtained 34 companies sampled in this study. Methods of data analysis using multiple linear regression analysis with a classic assumption test and path analysis. Hypothesis testing is done using the t-statistics, coefficient of determination (R2), and F-statistic. After the data were analyzed, it was found that the profitability has negative effect and does not significantly to capital structure, growth opportunity has significant and negative effect to the capital structure. Then profitability, growth opportunity and the capital structure influential partially positively and significantly to the firm value.